"Competing" for a robotics education. - Murphy, R.R (IEEE Robotics and automation magazine)
A strategy for integrating robot design competitions into courses in order to maximize learning experience and promote intellectual development is presented. The use of competitions fosters students' intellectual maturity, showing, inter alia, that there may be more than one correct answer to a problem